Beyond vision : going blind, inner seeing, and the nature of the self - Jones, Allan, 1943- (McGill-Queen's University Press, 2018)
"How does a young man who is losing his eyesight go about shaping a life? Such a dilemma is the stuff of "pathography," a dreary genre of literature that emphasizes suffering and loss. This literary convention and the misconceptions that fuel it are challenged by Allan Jones in his autobiography, Beyond Vision - Going Blind, Inner Seeing, and the Nature of the Self. Jones was Canada's first blind diplomat, and his vivid account of life and work in Tokyo, New Delhi and Ottawa is a testament to the blind person's native capacity for innovation and practical adjustment. But the deeper message of Beyond Vision is more radical and consequential: the self - the real self that is normally veiled - does not go blind. The deep self stands entirely apart from the experience of sightedness or blindness, as a centre of stable equanimity. This is what the author discovered through his study and assimilation of Indian Vedantic philosophy. Jones briefly describes the basic features of Advaita Vedanta, and identifies startling findings of contemporary science that are consonant with the Advaitic view of world and self. He then outlines practical applications of Advaita, for example the mindfulness practice that allowed him to retain his white cane mobility skills despite chronic and untreatable spinal and muscular pain. Beyond Vision is an intimate, many-sided personal and family biography. But the dominant feature of this book is the way the world changed out of all recognition, with the author as its fascinated explorer and laborialist."--